The Relation between Mind‐mindedness in Mothers with Borderline Personality Disorder and Mental State Understanding in their Children. Issue 1 (15th July 2012) - Schacht, Robin; Hammond, Linda; Marks, Maureen; Wood, Barbara; Conroy, Susan
Abstract : This study investigated relations between mind‐mindedness in mothers with borderline personality disorder (BPD) and mental state understanding in their children. Participants were 20 mothers with BPD and 19 mothers without personality disorder and their children, aged 39–61 months. Children's mental state understanding was examined via a battery of theory of mind and emotion labelling tasks. Maternal mind‐mindedness was assessed by mothers' use of mental state references to describe their children relative to other attributes. Maternal BPD was associated with fewer references to children's mental states as well as poorer levels of mental state understanding in their children. Findings lend some empirical support to recent theoretical suggestions that BPD is associated with a reduced capacity for mentalization, as well as reduced capacity for mental state understanding in children of mothers with BPD. Copyright © 2012 John Wiley & Sons, Ltd.